Discussion: “On interactive buckling in a sandwich structure” by C. D. Coman - Wadee, M. Ahmer; Yiatros, Stylianos (My University, 2011)
A recent article by Coman (Z Angew Math Phys 2009) on the response of compression sandwich struts made some claims on the quality of the simplified version of the interactive buckling model presented in Hunt and Wadee (Proc R Soc A 454(1972):1197–1216, 1998). Some of these claims are examined in detail herein; it is concluded that great care must be exercised when performing parametric studies with equations that have been derived from simplifying a mechanical model. This is because the resulting system of equations does not necessarily describe the original mechanical system in full, since the key assumptions necessarily change.
Keywords: Sandwich structures; Honeycomb structures; Sandwich beam